(untitled) (International Journal of Environmental Sciences, 2025)
In an era of escalating environmental challenges, digital marketing has emerged as a powerful instrument for promoting sustainability and influencing eco-conscious consumer behavior. This research investigates the transformative role of digital marketing in advancing environmental sustainability and cultivating green consumerism through a comprehensive mixed-methods approach. By analyzing the effectiveness of various digital channels—including social media, email marketing, content strategies, and e-commerce platforms—this study reveals how sustainability-focused digital campaigns significantly enhance consumer engagement, drive green purchasing intent, and contribute to circular economy objectives. Through quantitative analysis of 150 environmentally-engaged consumers and 50 marketing executives, complemented by qualitative case studies of pioneering brands (Patagonia, IKEA, and The Body Shop), the research demonstrates that digital marketing explains 71.8% of variance in sustainability awareness and shows strong correlations (r ≥ 0.84) between key digital channels and green purchase intentions. The findings establish digital marketing as not merely a commercial tool but a strategic catalyst for environmental education, policy advocacy, and sustainable development aligned with UN Sustainable Development Goals (SDGs). This study provides evidence-based recommendations for marketers, policymakers, and environmental advocates seeking to leverage digital platforms for meaningful ecological impact.